2018
DOI: 10.1007/s00253-018-8811-1
|View full text |Cite
|
Sign up to set email alerts
|

Applications of bacteriophages versus phage enzymes to combat and cure bacterial infections: an ambitious and also a realistic application?

Abstract: Bacteriophages (phages) are viruses that infect bacteria. The “predator–prey” interactions are recognized as a potentially effective way to treat infections. Phages, as well as phage-derived proteins, especially enzymes, are intensively studied to become future alternative or supportive antibacterials used alone or in combination with standard antibiotic regimens treatment. There are many publications presenting phage therapy aspects, and some papers focused separately on the application of phage-derived enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
132
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(142 citation statements)
references
References 151 publications
(181 reference statements)
0
132
1
5
Order By: Relevance
“…Accordingly, as shown in Figure S4, we found that the bactericidal concentration of TSPphg was approximately in a range of 30-80 µg/mL. Compared with recent studies [16,18,24,28], this concentration is at a relatively low level. For all tests, the log reduction for TSPphg treatment was measured after incubating different bacterial cells with 50 µg/mL TSPphg dissolved in PBS at 37 • C for 1 h, and three independent replicates were run in each reaction.…”
Section: Antibacterial Activity Of Tspphg Against Antibiotic-resistancontrasting
confidence: 39%
See 1 more Smart Citation
“…Accordingly, as shown in Figure S4, we found that the bactericidal concentration of TSPphg was approximately in a range of 30-80 µg/mL. Compared with recent studies [16,18,24,28], this concentration is at a relatively low level. For all tests, the log reduction for TSPphg treatment was measured after incubating different bacterial cells with 50 µg/mL TSPphg dissolved in PBS at 37 • C for 1 h, and three independent replicates were run in each reaction.…”
Section: Antibacterial Activity Of Tspphg Against Antibiotic-resistancontrasting
confidence: 39%
“…Due to the existence of a protective outer membrane (OM) that usually prevents a great number of antibiotics or drugs from entering Gram-negative bacterial cells, there is an increased interest in the identification and characterization of phage lysins that, as an alternative to conventional antibiotics, combat Gram-negative pathogens [29]. However, currently, the number of reported phage lysins that fight against Gram-positive bacteria is well over those of lysins against Gram-negative bacteria [28]. In this study, we found that TSPphg has considerable antimicrobial activity against both Gram-negative and Gram-positive bacteria; to our knowledge, it represents the first such lysin derived from the natural gene sequence in phage genome.…”
Section: Discussionmentioning
confidence: 99%
“…Phages, small viral entities that infect specific strains of bacteria, are abundant on our planet. They were discovered, independently, by Frederick William Twort (1915) and Félix d'Herelle (1917) [107,108]. Due to the immediate recognition of their potential as antibacterials, the treatment of many infections during the 1920s and 1930s was completed using phage therapy [108,109].…”
Section: Phage Therapymentioning
confidence: 99%
“…They were discovered, independently, by Frederick William Twort (1915) and Félix d'Herelle (1917) [107,108]. Due to the immediate recognition of their potential as antibacterials, the treatment of many infections during the 1920s and 1930s was completed using phage therapy [108,109]. Even though Western countries abandoned this therapeutic approach, research continued in many Eastern European countries and the former Soviet Union [108,109].…”
Section: Phage Therapymentioning
confidence: 99%
See 1 more Smart Citation